THE INFLUENCE OF TURNOVER, TASK COMMITMENT AND COOPERATION ON EMPLOYEE PERFORMANCE AT PT. THE GLORIOUS ENERGY NATURE OF BANGKA BELITUNG PROVINCE - Sabri, Sabri; Sumardin, Sumardin; Napitupulu, Ester Salonika; Arpah, M.; Aras, Mohamad (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of Turnover (X₁), Task Commitment (X₂), and Cooperation (X₃) on Employee Performance (Y) at PT. Alam Gemilang Energi. The company operates in the energy distribution sector and plays a strategic role in providing fuel in Pangkalpinang City. Employee performance is a critical factor in supporting the efficiency and effectiveness of the company's operations. This research uses a survey method with a quantitative approach. The research population includes all 47 employees of the company, with the sampling technique using a census. Data was collected through a questionnaire using a Likert scale and analyzed using descriptive statistical techniques, validity tests, reliability tests, simple linear regression, and multiple linear regression. The results show that Turnover (X₁) has a significant influence on Employee Performance with a t-value of 2.478 > t-table 1.67412 (p < 0.05), but only explains 8.1% of the variance in Employee Performance. Task Commitment (X₂) has a significant influence with a t-value of 5.794 > t-table 1.67412 (p < 0.05), explaining 32.4% of the variance in Employee Performance. Cooperation (X₃) has a significant influence with a t-value of 9.973 > t-table 1.67412 (p < 0.05), explaining 58.7% of the variance in Employee Performance. Collectively, the three independent variables explain 71.9% of the variance in Employee Performance (F-value = 58.027 > F-table = 2.79; p < 0.05). The conclusion of this study is that Turnover, Task Commitment, and Cooperation significantly influence Employee Performance at PT. Alam Gemilang Energi. Cooperation has the strongest influence, followed by Task Commitment and Turnover. Recommendations include better Turnover management, enhancing Task Commitment through rewards and training, and strengthening a collaborative work culture to improve Cooperation.